Coordination pattern of baseball pitching among young pitchers of various ages and velocity levels - Chen, H.-H.; Liu, C.; Yang, W.-W. (Journal of Sports Sciences, 2016)
This study compared the whole-body movement coordination of pitching among 72 baseball players of various ages and velocity levels. Participants were classified as senior, junior, and little according to their age, with each group comprising 24 players. The velocity levels of the high-velocity (the top eight) and low-velocity (the lowest eight) groups were classified according to their pitching velocity. During pitching, the coordinates of 15 markers attached to the major joints of the whole-body movement system were collected for analysis. Sixteen kinematic parameters were calculated to compare the groups and velocity levels. Principal component analysis (PCA) was conducted to quantify the coordination pattern of pitching movement. The results were as follows: (1) five position and two velocity parameters significantly differed among the age groups, and two position and one velocity parameters significantly differed between the high- and low-velocity groups. (2) The coordination patterns of pitching movement could be described using three components, of which the eigenvalues and contents varied according to age and velocity level. In conclusion, the senior and junior players showed greater elbow angular velocity, whereas the little players exhibited a wider shoulder angle only at the beginning of pitching. The players with high velocity exhibited higher trunk and shoulder rotation velocity. The variations among groups found using PCA and kinematics parameter analyses were consistent.